Two-step ball milling-assisted synthesis of N-doped biochar loaded with ferrous sulfide for enhanced adsorptive removal of Cr(Ⅵ) and tetracycline from water. (1st August 2022) - Qu, Jianhua; Zhang, Weihang; Bi, Fuxuan; Yan, Shaojuan; Miao, Xuemei; Zhang, Bo; Wang, Yifan; Ge, Chengjun; Zhang, Ying
Abstract: Nitrogen-doped biochar loaded with FeS (FeS@NBCBM ) was synthesized by two-step ball milling processes. Characterization results revealed that N-doping process successfully introduced pyridinic, pyrrolic, and graphitic N structures, and FeS was subsequently embedded in N-doped biochar (NBCBM ). The resultant FeS@NBCBM presented predominant adsorption capacity for Cr(VI) (194.69 mg/g) and tetracycline (TC, 371.29 mg/g) compared with BC (27.28 and 37.89 mg/g) and NBCBM (71.26 and 81.26 mg/g). In addition, the Cr(VI)/TC elimination process by FeS@NBCBM was basically stable with multiple co-existing ions with slight decrease on adsorption performance after three desorption-regeneration cycles. Most importantly, FeS@NBCBM was found to achieve Cr(VI) elimination not only by electrostatic attraction, ion exchange and complexation, but also by electrons-triggered reduction provided by different species of N, Fe 2+ as well as S(Ⅱ). Meantime, pore filling, hydrogen bonding, and π-π stacking interactions were demonstrated to contribute to TC adsorption. These results suggested the co-modification of N-doping and FeS loading by ball milling as an innovative decorating method for biochar to adsorptive purification of Cr(VI) and TC-contaminated water. Graphical abstract: Image 1 Highlights: N-doped biochar loaded with FeS is synthesized via a two-step ball milling method. FeS@NBCBM has high uptake for Cr(VI) (194.69 mg/g) and tetracycline (371.29 mg/g). FeS@NBCBM has good reusability and stability with disturbance of co-existing ions. Pyridinic N, pyrrolic N, and graphitic N contribute to Cr(VI) binding and reduction. Pore filling, hydrogen bonding, and π-π stacking interaction promote to TC binding.